(untitled) (Vietnam Journal of Community Medicine, 2025)
Background: To evaluate Anxiety among breast cancer patients at Tan Trieu K Hospital, Hanoi in 2024 and analysis of related factors. Methodology: A cross-sectional study was conducted on 405 breast cancer patients receiving treatment at Tan Trieu K Hospital, Hanoi from February to May 2024. Convenience sampling was used to select participants. Data was collected using a pre-designed questionnaire combining the Hospital Anxiety and Depression Scale (HADS). Results: The proportion of breast cancer patients with actual anxiety (abnormal cases) and signs of anxiety (borderline abnormal cases) were 31.1% and 26.7%. Multivariate regression analysis showed that factors related to patient anxiety include: living in rural areas versus urban areas (AOR=2.82; p<0.001), combined treatment with ≥ 2 methods compared to treatment with 1 method (AOR= 4.93; p<0.01). Recommendations: Regular psychological assessments should be conducted for patients undergoing treatment, especially those receiving combined therapies, to detect early signs of anxiety.